Sodium nitroprusside affects the level of anthocyanin and flavonol glycosides in pea (Pisum sativum L. cv. Arkel) leaves - Ganjewala, Deepak; Boba, Sunil; Raghavendra, Agepati S. (Acta Biologica Szegediensis, 2008)
The effects of sodium nitroprusside (SNP), a nitric oxide (NO) donor were investigated on the levels of anthocyanin and flavonol glycoside in pea (Pisum sativum L.) cv. Arkel leaves. The study was conducted in leaf discs (ca. 20 mm2) prepared from the youngest leaves. The anthocyanin and flavonol glycosides content diminish significantly ( 21% of each) in leaf discs following 1 mM SNP (1 mM) treatment for 3 h under light (600 μmol M-2.s-1). However, a huge increase both in the levels of anthocyanin and flavonol glycosides, 72 and 53% respectively was recorded after 2 h of 1 mM SNP treatment. 0.5 mM SNP treatment of the leaf discs did not change the anthocyanin level but considerable declined ( 13%) was observed in the level of flavonol glycosides as compared to the control. Surprisingly, the anthocyanin content in no SNP treated leaf discs after 3 h of incubation under light (600 μmol M-2.s-1) increased rapidly by 72% while flavonol glycosides content by 15% only. The photosynthetic capacities of SNP treated leaf discs were drastically inhibited. The study prelude that NO in combination of light influence the accumulation of anthocyanin and flavonol glycosides in pea leaves.